Winter aggregations, colony cycle, and seasonal phenotypic change in the paper wasp Polistes versicolor in subtropical Brazil - Gobbi, Nivar; Noll, Fernando B.; Penna, Marcelo A. H. (Springer, 2006)
Social wasps from temperate zones have clear annual colony cycles, and the young queens hibernate during winter. In the subtropics, the only previously reported evidence for the existence of hibernation is the facultative winter aggregations of females during harsh climate conditions. As in temperate-zone species analyzed so far, we show in this study that in the paper wasp, Polistes versicolor, a subtropical species, body size increases as an unfavorable season approaches. Our morphological studies indicate that larger females come from winter aggregations-that is, they are new queens. Multivariate analyses indicate that size is the only variable analyzed that shows a relationship to the differences. Given the absence of a harsh climate, we suggest that the occurrence of winter aggregations in tropical P. versicolor functions to allow some females to wait for better environmental conditions to start a new nest, rather than all being obliged to start a new nest as soon as they emerge.
Keywords: Polistes; paper wasps; winter congregations; life cycle; caste differences